Application of the DEB-TKTD model with multi-omics data: Prediction of life history traits of Chinese mitten crab (Eriocheir sinensis) under different salinities - Hanzun Zhang; Shipeng Dong; Hongwei Shan; Chao Yang; Fang Wang (Ecotoxicology and Environmental Safety)
Saline-alkaline aquaculture plays a crucial role in the ecological restoration of saline soils, yet high water salinity can significantly restrict the growth of cultured organisms. The Chinese mitten crab (Eriocheir sinensis) is typically farmed in freshwater, to evaluate the effects of salinity stress on these crabs, this study conducted laboratory aquaculture experiments at salinities of ≤ 0.5 (freshwater), 6, 12, and 18 ‰. Regular data on crab survival and growth were collected over 35 days. Subsequently, tissues including the eyestalk, posterior gill, hepatopancreas, and ovary were sampled from crabs in both the freshwater control group and the 18 ‰ salinity treatment group for transcriptional and metabolomic analysis. The omics data were used to ascertain the physiological mode of action (pMoA) affected by salinity in the crabs. A dynamic energy budget toxicokinetic-toxicodynamic (DEB-TKTD) model was built based on these pMoAs to predict the life history traits of crabs across different salinities, including survival, growth, and reproduction. The omics results indicated that at 18 ‰, the osmoregulatory capacity and oxidative stress resistance were enhanced, and vitellogenin synthesis was stimulated. This suggests that the two pMoAs involved increasing maintenance costs and reallocating energy between soma and reproduction. DEB-TKTD model predictions fit well with the observed data, with high R2 values (0.9704 for survival, 0.9842 for carapace width, and 0.9283 for reproduction) and low NRMSE (0.0093, 0.1175, and 0.0778, respectively). The predictions indicate that after 60 days, survival rates under salinities of 6, 12, and 18 ‰ decreased by 35.7 %, 56.7 %, and 66.2 %, respectively, compared to freshwater conditions. Growth in carapace width was similarly affected, with reductions of 21.5 %, 42.3 %, and 62.5 %, respectively. The maturation process was accelerated for crabs in saline conditions, with puberty achieved at 45, 36, and 31 days, compared to the freshwater group that had not matured. Furthermore, the LC50 for salinity decreased from 9.07 ‰ (95 % CI: 7.33–10.15 ‰) at 35 days to 4.59 ‰ (95 % CI: 3.12–5.83 ‰) at 60 days. The findings of this study indicate the significant impact of salinity on the survival, growth, and maturation of Chinese mitten crabs by altering maintenance costs and energy allocation. The DEB-TKTD model, informed by omics data, accurately predicts the life history traits of crabs under saline stress. This approach provides an innovative tool for ecological toxicological research in the aquaculture environment.